Media in dictatorial regimes: Case study of North Korea, Turkmenistan, and Russia - Kreishan, Asem Khaleel (Eximia, 2022)
This study is A qualitative method used for this study to explore the freedom of media in North Korea, Turkmenistan, and Russia, In today's world, the media plays a significant part in the conduct of contemporary warfare by tilting the balance of public opinion in favor of certain camps. In North Korea, Russia, and Turkmenistan, the purpose of this research is to determine the degree to which freedom of speech and the degree to which media freedoms impact the perceived significance of journalists about a variety of characteristics. And because freedoms of media and expression are non-existent in these countries, which are repressive states according to the order of indicators of many organizations, associations, and centers of studies concerned with human rights, in particular, this study analyses the degree of freedom of expression as well as the perceived credibility of journalists for their sources on their perceptions of the various features of North Korea, Russia, and Turkmenistan, even after control has been exercised. To investigate these concerns, he disclosed information on media freedoms in North Korea, Russia, and Turkmenistan. The findings indicate that the amount of impact exerted by various elements at various levels might change depending on the topics or parts of issues that are covered by journalists. In the cases of North Korea, Russia, and Turkmenistan, sources operating at the institutional level had a considerable influence on the perceived significance of the rogue state aspect of North Korea, Russia, and Turkmenistan among journalists. When compared, the nationality of journalists working at the social system level was a more accurate predictor of the perceived relevance of journalists to the conversation partner factor in North Korea, Russia, and Turkmenistan.